Distributed parameter-based voltage stability index for identification of critical lines and voltage stability margin in power system. Issue 1 (1st January 2018) - Singh, Pradeep; Tiwari, Rajive
Abstract: This paper proposes a distributed parameter-based voltage stability index ( DPVSI ) for assessment of voltage stability of the power system. Proposed index incorporates the effects of distributed parameters of transmission line to predict voltage collapse. Critical loading of different lines is determined by raising active/reactive loading of different lines till the index reaches its critical value. Different contingencies are also ranked on the basis of index. Reactive power margin of the system is measured by mapping the index value in terms of reactive power margin of the system. The proposed index is investigated on IEEE 30-bus and 118-bus test systems to prove its potential.